Hospital and Community Pharmacists' Views of and Perspectives on the Establishment of an Intraprofessional Collaboration in the Transition of Care for Newly Discharged Patients - Laura V.J. Lech; Gitte R. Husted; Anna Birna Almarsdottír; Trine R.H. Andersen; Charlotte Rossing; Lotte S. Nørgaard (University of Minnesota Libraries Publishing, 2020)
Background Hospital and community pharmacists are increasingly involved in patients' medication interventions related to the transition of care from the hospital to a patient's home. These interventions may enable pharmacists to collaborate across healthcare sector boundaries. However, little is known about pharmacists' views on intraprofessional collaboration across healthcare sectors and what affects the establishment of such collaboration. Objectives The aim of this study was to understand the views and perspectives of hospital pharmacists (HPs) and community pharmacists (CPs) on establishing an intraprofessional collaboration in relation to newly discharging patients.  Methods Joint focus group interviews with HPs and CPs in the Zealand region of Denmark were conducted. The HPs were employed at the only hospital pharmacy in the region (Region Zealand Hospital Pharmacy). Five HPs and six CPs participated in two focus groups. The focus groups were analyzed using theoretical thematic analysis. Results Three themes and seven subthemes were identified. The first theme, "Context", was divided into two subthemes: "Prioritization of new tasks in the intraprofessional collaboration" and "The lack of insight into the patient's hospital stay". The second theme, "The hospital physicians and GPs as the focal points for the HPs' and CPs' work", was divided into three subthemes: "The limitation of the CPs and HPs based on current roles and organizations", "Lack of regular access to the physician gives the patients more responsibility" and "Lack of support from the GPs for the work conducted by HPs and CPs". The last theme, "Individuals", had two subthemes: "The motivation for working intraprofessionally" and "CPs' hesitancy towards the new tasks in the intraprofessional collaboration".  Conclusion Both HPs and CPs are highly influenced by their work context in regard to establishing a new intraprofessional collaboration. Limited resources for intraprofessional collaboration should be taken into account. Likewise, the collaboration should fit into daily routines, which may eliminate hesitancy towards new forms of collaboration and tasks shared between HPs and CPs. The physician was identified as an important key professional, since the work tasks of both HPs and CPs depend on the physician, which in turn limits the capability and success of solely intraprofessional collaboration.   Original Research